ОЦІНКА ВТРАТ ЕЛЕКТРОЕНЕРГІЇ НА КОРОНУ В ПЛ 220–750 КВ З УРАХУВАННЯМ КОНСТРУКТИВНИХ ПАРАМЕТРІВ ОПОР - Кучанський, В.В.; Гай, О.В.; Бодунов , В.М.; Ворушило, А.О.; Гай, Г.А. (Інститут електродинаміки Національної академії наук України, 2025)
The article describes an improved mathematical model for estimating climatic losses of electric energy on the crown in overhead power lines. The model is supplemented by taking into account the equivalent height of the wire above the ground h according to the parameters given in the Rules for the «Arrangement of Electrical Installations (PUE)», as well as the possibility of calculating processes in three phases using the method of symmetrical components. The procedure for determining the initial electric field strength on the surface of wires for bad weather conditions is specified. The significant influence on the results of calculations of electrical energy losses on the crown of the supports and the presence of a lightning protection cable (GZT) is proven. The results obtained indicate the feasibility of taking into account the configuration of the supports and the presence of GZT when forming tabular values ​​of specific power losses and average annual specific losses on the crown given in regulatory documents, which will increase the accuracy of estimating climatic losses of electric energy. Ref. 20, tabl. 3, fig. 4.